Lignin phenols as a basis for biopreparations - Kovalev, Ivan V.; Kovaleva, Natalia O. (Experimental Biology and Biotechnology, 2021)
The content and composition of lignin phenols in plants and soils of latitudinal zones and vertical natural zones of the North Caucasus and Northwest Tien Shan have been studied. The special role of lignin phenols of underground plant organs in the process of humification was revealed. It was shown that the oxidation degree of the biopolymer increases during the transformation of organic matter from living plant tissues to humic acids in soils. The fraction of lignin fragments that remain unchanged during the biotransformation of the polymer in the row plant tissues – fall – litter – soils – humic acids – buried humic acids is calculated. It has also been demonstrated that the biochemical composition of plants has a decisive effect on the structure of humic acids in soils. With the help of quantitative analysis of lignin phenols and 13C NMR spectroscopy, it is proved that lignin of higher plants is involved in the formation of humic acids, both aliphatic and aromatic parts of molecules. The areas of application of lignin phenols in the practice of agriculture and medicine are proposed.
Keywords: lignin phenols; transformation of lignin; humic acids; biomarkers; soil fertility